1997
DOI: 10.1007/bf00056425
|View full text |Cite
|
Sign up to set email alerts
|

Screening of bacteria, isolated from PAH-contaminated soils, for production of biosurfactants and bioemulsifiers

Abstract: Fifty-seven bacterial strains were isolated from PAH-contaminated soils using PAl-I-amended minimal medium. The isolates were screened for their production of biosurfactants and bioemulsifiers when grown in liquid media containing selected PAHs. The results suggest that many, but not all, of the isolates are able to produce biosurfactants or bioemulsifiers under the experimental conditions. The majority of the strains isolated on phenanthrene, pyrene, and fluoranthene were better emulsifiers than surface tensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
112
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(128 citation statements)
references
References 35 publications
(19 reference statements)
9
112
0
4
Order By: Relevance
“…The capacity of the hydrolysates to emulsify hydrophobic substances was tested. Each hydrolysate was mixed with 2 mL of soybean oil and allowed to stand for 24 h at room temperature (Willumsen and Karlson 1997). After this time the emulsifying index (E24) was determined as: E24−(height of the layer/ height of the total)×100.…”
Section: Determination Of Emulsifying and Foaming Capacitiesmentioning
confidence: 99%
“…The capacity of the hydrolysates to emulsify hydrophobic substances was tested. Each hydrolysate was mixed with 2 mL of soybean oil and allowed to stand for 24 h at room temperature (Willumsen and Karlson 1997). After this time the emulsifying index (E24) was determined as: E24−(height of the layer/ height of the total)×100.…”
Section: Determination Of Emulsifying and Foaming Capacitiesmentioning
confidence: 99%
“…The criterion used for selecting biosurfactant producers is the ability to reduce the surface tension below 40 mN m-1 [16,9] while a criterion cited for emulsionstabilizing capacity is the ability to maintain at least 50% of the original emulsion volume 24 h after formation [56]. Strains were cultivated on the standard medium and screening of biosurfactant producing colonies was performed using the qualitative drop-collapse test described by Jain et al [33] after being modified by Bodour and Maier [9].…”
Section: Morphological Biochemical and Physiological Characterizationmentioning
confidence: 99%
“…Also, Willumsen and Karlson [56], a criterion cited for emulsion-stabilizing capacity is the ability to maintain at least 50% of the original emulsion volume 24h after formation. The 2 strains tested produced extracellular biosurfactant and produced a strong biosurfactant capable of generating a stable emulsion over several hours.…”
Section: Characterization Of Isolatesmentioning
confidence: 99%
“…Allen et al (37) found that all microbial isolates from subsurface soil contaminated with unleaded gasoline showed emulsification activity when overlaid with gasoline, whereas emulsification activity by microbial cultures overlaid with kerosene and diesel fuel were weaker. Willumsen and Karlson (40) found that 67% of their isolates were able to form detectable emulsions with diesel fuel. One might speculate that this relatively low percentage of emulsifiers among isolates from soil contaminated with PAH as opposed to soil contaminated with aliphatic hydrocarbons might indicate that growth on PAH does not require emulsification to the same extent as growth on aliphatic hydrocarbons.…”
Section: Ds10-129mentioning
confidence: 99%